Reflections on Literature Textbooks in the Journal "Maorif va o‘qitg‘uvchi" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, information about the journal "Maorif va O‘qitg‘uvchi" is provided, along with statistics on the literary and pedagogical critical articles published in the journal between 1925 and 1929. The article also discusses the book "Adabiyot to‘g‘risida xato nazariyalar" by G‘ozi Olim, published in the 2nd issue of the magazine in 1925, which is also a criticism of the work "Amaliy ham nazariy adabiyot darslari" by Abdurakhmon Sa'diy, published in 1924, intended for high schools. Furthermore, The articles "Birinchi "O’rnak" darsligi, "Ikinchi "O’rnak" darsligi" and "Uchinchi "O’rnak" darsligi" about the "O‘rnak" textbooks for grades 1-3 written by Elbek, published in issues 2-5-6-7 of 1926, and critical articles by E. Sayid about the "Bilim" textbook written by Elbek, published in issue 2 of 1928, were analyzed. Reactions to critical opinions about textbooks were expressed.